2010
DOI: 10.1002/pits.20543
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of silent versus aloud reading comprehension of elementary students using Maze assessment procedures

Abstract: Many reading comprehension measures require the student to read silently. When students read silently, important information (e.g., consistent reading errors) may not be identified. It may also be difficult to detect a student who is choosing not to read the passage. For this reason, investigating whether there is a significant difference in comprehension under silent and aloud reading conditions is important to determine under what conditions reading comprehension should be measured accurately. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The results of such comparisons are mixed. Lynn Fuchs, Douglas Fuchs and Linn Maxwell (1988) found that when the reading levels of oral and silent passages were equated, the correlation between comprehension scores was generally high, a finding echoed in more recent studies (Hale et al 2011;McCallum et al 2004). However, among middle-school students (i.e., grades 6-8 or ages 11-14), Carolyn Denton et al (2011) found that ORF was more strongly related to reading comprehension than to scores on a silent task, results similar to those of a number of other studies (Ardoin et al 2004;Hale et al 2007;Jenkins and Jewell 1993).…”
Section: Background and Contextmentioning
confidence: 64%
“…The results of such comparisons are mixed. Lynn Fuchs, Douglas Fuchs and Linn Maxwell (1988) found that when the reading levels of oral and silent passages were equated, the correlation between comprehension scores was generally high, a finding echoed in more recent studies (Hale et al 2011;McCallum et al 2004). However, among middle-school students (i.e., grades 6-8 or ages 11-14), Carolyn Denton et al (2011) found that ORF was more strongly related to reading comprehension than to scores on a silent task, results similar to those of a number of other studies (Ardoin et al 2004;Hale et al 2007;Jenkins and Jewell 1993).…”
Section: Background and Contextmentioning
confidence: 64%
“…Conversely, if students can passively rely on the teacher to process the text, they might develop a sense of learned helplessness in which they maintain low expectations for their reading abilities and do not persist when encountering difficulties (Butkowsky & Willows, 1980). However, there are inconclusive results from research examining whether oral or silent reading contributes to better reading comprehension performance (Hale et al, 2011; McCallum, Sharp, Bell, & George, 2004). Moreover, the studies primarily have focused on testing rather than learning situations and have not included large numbers of students who are not native English speakers.…”
Section: Potential Problems With Teacher Read-aloudsmentioning
confidence: 99%
“…They observed significant differences for the linguistic material and the administration procedure (i.e., reading aloud or silently, and test time). However, this was not upheld for CBM-Maze tasks because research has not found significant differences for primary students between reading silently or aloud (Hale et al, 2011). Accordingly, the CBM-Maze assessments are mostly administered silently for higher practicability in group settings.…”
Section: Test Administrationmentioning
confidence: 99%